Effect of graphene oxide nanoparticles on blast load resistance of steel fiber reinforced concrete - Jamnam, Sittisak; Maho, Buchit; Techaphatthanakon, Apisit; Ruttanapun, Chesta; Aemlaor, Peerasak; Zhang, Hexin; Sukontasukkul, Piti (My University, 2022)
Concrete structures may occasionally be subjected to both intentional or unintentional explosions which could cause casualties and damage to properties. Advance research on protective structures are important to enhance blast resistance of materials, and to protect life and properties. This study investigated the effect of graphene oxide nanoparticles (GO) on enhancing the blast resistance of fiber reinforced cement mortar (FRM). GO in solution was incorporated in steel fiber reinforced mortar at the rate of 0, 0.025, 0.050, 0.075, and 0.100 % by weight of cement. A series of experiments were carried out consisting of 2 stages: Stage 1) workability, setting time, compressive and flexural strength, and microstructure using SEM and XRD processes, and Stage 2) blasting loading test. The optimum GO dosage giving the highest compressive and flexural strengths from the 1st stage was determined and chosen to continue on the 2nd stage (blast loading test). The blasting tests were performed on panel specimens (500mmx1000mmx60mm) using TNT weighing ½ lb. (226.7 g) with three different standoff distances of 340, 400, and 460 mm. Results from Stage 1 on both flexural and compression tests indicated an optimum GO content of 0.025% by weight of cement. The workability was found to decrease with the increasing the GO content. The SEM images also revealed that the addition of GO nanoparticles reduced the porosity in the mortar matrix. For the blasting test, three damage patterns were observed: complete flexural failure, partial damage (flexural cracking), and no major damage, depending on the standoff distance and specimen type. The addition of GO can reduce the maximum and permanent deflections of the panel under blast loading. FRM panels with GO at 0.025% tested at the standoff distance of 460 mm showed the lowest level of damage.
Keywords: Blast loading; Blast resistance; Fiber reinforced mortar; Graphene oxide; Non-contact detonation; Steel fiber; TNT